Pengaruh inventarisasi aset, penggunaan aset, pengamanan dan pemeliharaan aset terhadap optimalisasi aset tetap tanah pada pemerintah Kabupaten Malang - Wicaksana, Arif; Harmono, Harmono; Yuniarti, Sari (Universitas Merdeka Malang, 2021)
In the era of national transformation and regional autonomy, there have been many breakthroughs in the management of land fixed assets, but many financial problems and land assets have not been implemented optimally, effectively and efficiently in their management. This study was used to analyze the effect of asset management on the optimization of fixed land assets in Malang Regency Government. The independent variables used in this study were asset inventory, asset use, asset security, and maintenance, while the dependent variable used asset utilization and asset optimization with a sample of 62 respondents. This type of research is quantitative using multiple regression analysis and path analysis method. The results showed that there was an indirect effect of asset inventory, asset use, and asset security and maintenance on asset optimization through asset utilization where security and asset maintenance had a significant and positive effect, while asset inventory and asset use had no effect on asset optimization. The direct effect of asset inventory, asset use, asset security, and maintenance on asset optimization shows that asset inventory and asset security have a significant and positive effect on asset optimization, while asset use has no effect on asset optimization. In addition, asset utilization has a significant and positive effect on asset optimization.